Innovacionnaja metodika soveršenstvovanija techniki legkoatleticeskich pryžkov - Ogandzhanov, A. L. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2017)
Modern equipment based on computer technology can significantly improve the efficiency and accuracy of complex control procedures in athletics jumps. The study is devoted to the development of techniques for improving the technical training of jumper athletes on the basis of the innovative measuring system "OptoJump Next".